Investigation of Sandstone Mesostructure Damage Caused by Freeze-Thaw Cycles via CT Image Enhancement Technology. (15th October 2020) - Liu, Hui; Yang, Gengshe; Yun, Yehui; Lin, Jianghao; Ye, Wanjun; Zhang, Huimei; Zhang, Yao
Abstract : The mesostructures of rocks determine their macromechanical properties. These rock mesostructures may be altered by the freeze-thaw cycles in cold regions. In this regard, this paper proposes a quantitative evaluation method based on computed tomography (CT) scanning technology for investigating the mesostructure and damage characteristics of sandstone subjected to freeze-thaw conditions. CT scan images of two sandstones with different grain sizes were obtained after 0, 20, 40, 60, 80, and 100 freeze-thaw cycles, using a high-precision CT scanner. Based on the microphysical information contained in these CT images, pseudo-color-enhancement of the CT images of rocks subjected to freeze-thaw cycles was realized. The use of such a pseudo-color-enhancement technique can improve the resolution of CT images. Thus, particle detachment, crack initiation, crack propagation, and increased porosity due to the volumetric expansion of water inside the rock could be detected and clearly observed. Furthermore, a numerical expression for the mesostructure and damage information contained in the pseudo-color-enhanced images is presented herein; this serves as a convenient method for quantitative analyses of sandstone damage under freeze-thaw cycles. An analysis of the pseudo-color-enhanced images shows that, under freeze-thaw cycles, damage propagation in sandstone originates from existing damage or defect sites. After the stages of crack (pore) formation, penetration, and propagation, the freeze-thaw cycle-induced damage increases gradually, while the effective bearing area of the rock decreases continuously. Herein, a schematic of a conceptual model for the freeze-thaw cycle-induced deterioration in sandstone mesostructures is presented. Damage propagation models for sandstones with two different grain sizes subjected to freeze-thaw cycles were also developed. Based on the damage mechanics theory, a damage variable expressed in terms of the pore area was defined. Moreover, the relationship between this damage variable and the freeze-thaw cycles was established.